Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1155/2018/5980636
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical Criticality in Gene Regulatory Networks

Abstract: A well-known hypothesis, with far-reaching implications, is that biological evolution should preferentially lead to states that are dynamically critical. In previous papers, we showed that a well-known model of genetic regulatory networks, namely, that of random Boolean networks, allows one to study in depth the relationship between the dynamical regime of a living being’s gene network and its response to permanent perturbations. In this paper, we analyze a huge set of new experimental data on single gene knoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 62 publications
(102 reference statements)
2
29
0
Order By: Relevance
“…In the case of several models of type (a), which describe specific genetic circuits, a wide analysis by [15] has shown that the (static) sensitivity is close to 1. Similar results were obtained using models of type (b), i.e., RBNs, which were applied to describe the effects of gene perturbations induced by permanently inhibiting the expression of a single gene (knock-out) and by observing the changes of the expression levels of the other genes [12,14,16,30].…”
Section: Boolean Models Of Gene Regulatory Networksupporting
confidence: 58%
See 1 more Smart Citation
“…In the case of several models of type (a), which describe specific genetic circuits, a wide analysis by [15] has shown that the (static) sensitivity is close to 1. Similar results were obtained using models of type (b), i.e., RBNs, which were applied to describe the effects of gene perturbations induced by permanently inhibiting the expression of a single gene (knock-out) and by observing the changes of the expression levels of the other genes [12,14,16,30].…”
Section: Boolean Models Of Gene Regulatory Networksupporting
confidence: 58%
“…In this way, it is possible to use a static measure (the size of avalanches) to draw inferences about the dynamical regime of the network. This has been discussed in a series of papers, and it has been shown that it works in the well-studied case of the yeast S. Cerevisiae [12,14,16]. The best estimate of the Derrida parameter places it in the ordered region, quite close to the critical boundary [16].…”
Section: Boolean Models Of Gene Regulatory Networkmentioning
confidence: 99%
“…This can be understood because immune cells probably not only have a variable environment, but actually have evolved to thrive on it. The finding on the ordered dynamics of the CD4+ Tcell network is consistent with many research findings exhibiting that gene regulatory networks of biological systems have ordered or critical dynamics [49][50][51][52].…”
Section: Comparison Of Antifragility Between Multilayer and Single-lasupporting
confidence: 90%
“…We found that A. thaliana cell-cycle repeatedly produces antifragile networks at regular intervals depending on the values of . Based on many studies demonstrating living organisms are ordered or critical [47][48][49][50], we can infer that A. thaliana might have been evolved in environments where particular dimensions of perturbations are added more frequently than other biological systems. We also found that CD4+ T cell differentiation and plasticity is the most antifragile of the ones studied, probably because it has the most variable environment.…”
Section: Antifragility In Biological Bnsmentioning
confidence: 99%